Serve ball trajectory characteristics of different volleyballs and their causes - Tamaru, T.; Ito, S.; Hiratsuka, M. (Proceedings, 2020)
Volleyball is a sport that starts with a serve, so effective service is essential to win the game. The trajectory of the ball is complicatedly affected by the fluid force, which depends on the speed, spin speed, and panel shape. To understand the aerodynamic characteristics of the ball and to propose an ideal serve method, we measured the fluid force and flight trajectory. The fluid force applied to the ball was measured at a wind speed of 4-30 m/s in the wind tunnel. The fluid force on the ball was strongly dependent on the ball type and orientation of the panel. In the flight trajectory measurement, the trajectory of the ball was measured using a high-speed camera under controlled speed and spin speed using a shotting machine. The effect of the panel orientation shown by the fluid force measurement was consistent with the results of the trajectory analysis, clarifying the importance of the panel orientation in serving.